2005
DOI: 10.1111/j.1540-8183.2005.04070.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Left Main Occlusion During Percutaneous Coronary Intervention Associated with Heparin Induced Thrombocytopenia with Thrombosis Syndrome

Abstract: A 76-year-old male was admitted with Braunwald IIIB unstable angina and treated with intravenous heparin. Coronary angiography 20 days later revealed a severe stenosis in the left circumflex artery. During coronary angioplasty thrombus developed in the circumflex artery, extended in the left main and lead to its occlusion. Normal left coronary artery patency and flow were achieved after intracoronary and intravenous administration of abciximab, and multiple stenting. Platelet-count decrease and an ELISA assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…9 however, involvement of the coronary circulation is extremely rare; in the setting of postcardiac transplantation hitt syndrome, coronary artery thrombosis has only been reported in association with percutaneous coronary interventions and to our knowledge has not been reported as a spontaneous occurrence. 10,11 Conclusion our patient suffered intracoronary thrombosis early after cardiac transplantation in the absence of overt pre-existing coronary artery disease. the nature of this event was most likely multifactorial and due to prolonged ischemia time, donor brain death, cytomegalovirus mismatch, and acute allograft cellular rejection.…”
Section: Discussionmentioning
confidence: 80%
“…9 however, involvement of the coronary circulation is extremely rare; in the setting of postcardiac transplantation hitt syndrome, coronary artery thrombosis has only been reported in association with percutaneous coronary interventions and to our knowledge has not been reported as a spontaneous occurrence. 10,11 Conclusion our patient suffered intracoronary thrombosis early after cardiac transplantation in the absence of overt pre-existing coronary artery disease. the nature of this event was most likely multifactorial and due to prolonged ischemia time, donor brain death, cytomegalovirus mismatch, and acute allograft cellular rejection.…”
Section: Discussionmentioning
confidence: 80%
“…This can manifest in acute myocardial ischaemia and can be a life-threatening emergency when it occurs. There had been previous reported cases of HIT causing coronary thrombus formation, however most in the setting of either previous coronary intervention, stenting or in coronary bypass grafts 4–10 …”
Section: Discussionmentioning
confidence: 99%
“…Venous thrombosis is far more common than arterial thrombosis in HIT, although both occur. In patients with HIT, native coronary arteries are rarely implicated by thrombus formation and this almost always occurs in the setting of venous coronary grafts or previous coronary interventions 4–10 . Here, we describe a case of thrombus formation in a native coronary artery causing an ST-elevation myocardial infarct (STEMI) secondary to HIT.…”
Section: Introductionmentioning
confidence: 99%
“…Sakai et al (9) reported a case of inferior acute myocardial infarction where thrombi appeared in the LCX and LAD 40 minutes after readministration of heparin during elective PCI, which was performed 21 days after conservative treatment with heparin. Ziakas et al (10) described a case of unstable angina where thrombi appeared in the LCX and in the left main trunk of the coronary artery 50 minutes after readministration of heparin during elective PCI. Mibiki et al (11) also reported a case of acute simultaneous thrombosis of three coronary vessels during elective PCI on day 17.…”
Section: Discussionmentioning
confidence: 99%